Discourse, Culture and Organization Inquiries into Relational Structures of Power - Marttila, Tomas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'A highly original contribution to the field of discourse analysis and an important milestone for the presentation and systematization of the Essex School with contributions from an outstanding range of scholars from different countries and disciplines.' -Daniel Wrana, The Martin Luther University of Halle-Wittenberg, Germany This edited volume brings together leading international researchers from across the social sciences to examine the theoretical premises, methodological options and critical potentials of the Essex School of discourse analysis, founded on the work of Ernesto Laclau and Chantal Mouffe. In doing so, it presents a clear picture of a poststructuralist and post-foundational research program to postdisciplinary discourse research. Divided into three parts, it begins by elaborating the ontological, theoretical and methodological foundations of the Essex School's approach to discourse analysis. The second part provides empirical case studies showing how the Essex School research program informs and instructs empirical discourse research. In the concluding third part authors explain how and with what possible consequences this strand of discourse research contributes to social practices of critique. It offers a crucial contribution to the further methodologization and operationalization of the Essex School's approach so as to make it a viable alternative to discourse-analytical approaches that take dominant positions in today's 'field of discourse studies'. The book's transdisciplinary focus will attract readers who use discourse analysis in all areas of the social sciences and humanities, particularly applied linguistics, cultural anthropology, sociology, philosophy and history. Tomas Marttila is Senior Lecturer in sociology at the Ludwig Maximilian University of Munich, Germany. .
Chapter 1: Introduction to the Volume; Tomas Marttila -- Part I: Foundations -- Chapter 2: Post-foundational Discourse Analysis: Theoretical Premises and Methodological Options; Tomas Marttila -- Chapter 3: Discourse and Heterogeneity; Lasse Thomassen -- Chapter 4: Hegemony Analysis: Theory, Methodology and Research Practice; Martin Nonhoff -- Chapter 5: The Retroductive Cycle: The Research Process in Poststructuralist Discourse Analysis; Jason Glynos and David Howarth; Part II: Case Studies: Culture, Politics, Populism -- Chapter 6: Eating Power: Food, Culture and Politics; Fabio Parasecoli -- Chapter 7: About Dislocations and Invitations: Deepening the Conceptualization of the Discursive-Material Knot; Nico Carpentier -- Chapter 8: Rhetorical-performative Analysis of the Urban Symbolic Landscape: Populism in Action; Emilia Palonen; Chapter 9: Solidarity in Europe and the Role of Immigration Policies: A Discourse Theoretical Perspective; Efharis Mascha -- Chapter 10: 'The People' and its Antagonistic Other: The Populist Right-wing Movement Pegida in Germany; Ronald Hartz -- Chapter 11: Cultural Differences in German Discourses on Refugees: A Political Geographical Perspective;Annika Mattissek and Tobias Schopper -- Chapter 12: Populism vs. Anti-populism in the Greek Press: Post-Structuralist Discourse Theory Meets Corpus Linguistics; Nikos Nikisianis, Thomas Siomos, Yannis Stavrakakis, Titika Dimitroulia and Grigoris Markou -- Part III: Possibilities Of Critique -- Chapter 13: Tensions in the Post-Althusserian Project: Descriptive Indeterminacy and Normative Uncertainty; Geoff Boucher -- Chapter 14: Post-foundationalism and the Possibility of Critique: Comparing Laclau and Mouffe; Marius Hildebrand and Astrid Séville -- Chapter 15: Post-foundationalism, System Theory and the Impossibility of Critique; Niels Åkerstrøm Andersen, Erik Højbjerg and Anders la Cour.
Keywords: Linguistics -- Methodology; Language and languages -- Philosophy; Sociology -- Methodology; Poststructuralism; Philosophy and social sciences; Political sociology; Research Methods in Language and Linguistics; Philosophy of Language; Sociological Methods; Poststructuralism; Philosophy of the Social Sciences; Political Sociology